Creation language in Romans 8 : a study in Monosemy - Fewster, Gregory P. (Linguistic Biblical Studies, 2013)
Modern scholarship tends to understand Paul's use of creation language (κτίσις) in Rom 8.18-23 as part of a commentary on the state of sub-human creation. This misguided position warrants an inquiry into the state of lexical study in New Testament scholarship. As a result, Fewster articulates a theory of lexical monosemy, cast in the framework of Systemic Functional Linguistics. The model is applied to Paul's use of κτίσις through a robust corpus analysis and investigation into the word's role within the paragraph. κτίσις contributes to the cohesive structure of Rom 8.18-23 and-contra the majority of interpreters-functions as a metaphor for the human body.